2016
DOI: 10.1002/cctc.201601183
|View full text |Cite
|
Sign up to set email alerts
|

N‐Oxyl‐Radical‐Catalyzed Intermolecular Aminooxygenation of Styrenes and Inter/intramolecular Aminoalkoxylation of Homoallylic Alcohols

Abstract: By taking advantage of the redox cycle between the reductive N‐oxyl radical and its oxidative oxoammonium counterpart, the N‐oxyl‐radical‐catalyzed intermolecular aminohydroxylation of styrenes with N‐fluorobenzenesulfonimide was developed. Various vinyl arenes were aminohydroxylated in moderate to excellent yields with high regio‐ and diastereoselectivities by using environmentally benign H2O as the oxygen source. In addition, the sequential inter/intramolecular aminoalkoxylation of homoallylic alcohols was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…[33] The reaction between 1 and TEMPO leads to complete conversion of 1,a s judged by 19 FNMR spectroscopy,a nd the formation of oxoammonium salt [22]BF 4 (Scheme 10 a) as judged by the comparisono fI Ra nd UV spectra with those of an authentic sample prepared by the reactiono fT EMPO with bleach and tetrafluoroboric acid (Scheme 10 b). [43] The use of TEMPO as a radicalt rap in reactions mediated by 1 is therefore unreliable. However,w hile [ 22]ClO 4 reacts with vinyl azides to form various functionalised products, [44] [22]BF 4 reacts with 8c and 18 to form the corresponding naphthalenes 23 and 24 (Scheme10c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[33] The reaction between 1 and TEMPO leads to complete conversion of 1,a s judged by 19 FNMR spectroscopy,a nd the formation of oxoammonium salt [22]BF 4 (Scheme 10 a) as judged by the comparisono fI Ra nd UV spectra with those of an authentic sample prepared by the reactiono fT EMPO with bleach and tetrafluoroboric acid (Scheme 10 b). [43] The use of TEMPO as a radicalt rap in reactions mediated by 1 is therefore unreliable. However,w hile [ 22]ClO 4 reacts with vinyl azides to form various functionalised products, [44] [22]BF 4 reacts with 8c and 18 to form the corresponding naphthalenes 23 and 24 (Scheme10c).…”
Section: Resultsmentioning
confidence: 99%
“…Although the reaction did indeed cease completely upon the addition of TEMPO, this was due to the immediate and complete destruction of 1 . The reaction between 1 and TEMPO leads to complete conversion of 1 , as judged by 19 F NMR spectroscopy, and the formation of oxoammonium salt [ 22 ]BF 4 (Scheme a) as judged by the comparison of IR and UV spectra with those of an authentic sample prepared by the reaction of TEMPO with bleach and tetrafluoroboric acid (Scheme b) . The use of TEMPO as a radical trap in reactions mediated by 1 is therefore unreliable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Weng and Zhang reported a 4-substituted TEMPO-catalyzed intermolecular aminooxygenation of styrenes and inter/intramolecular aminoalkoxylation of homoallylic alcohols using N-fluorobenzenesulfonimide (NFSI) as an oxidant and aminating reagent. 218 This reaction is based on a similar stoichiometric reaction using TEMPO-Na reported by Studer et al 219,220 The authors accomplished the catalytic transformation using an external nucleophile (H2O and pendant alcohol). In 2017, Zhang et al reported a TEMPO + -mediated tandem cyclization of β-oxoamides with amine hydrochlorides to yield pyrrolin-4-ones.…”
Section: -7-1 Oxidation Of Organosulfur Compoundsmentioning
confidence: 99%